PHYSICS AND CHEMICAL, IMMUNOENZYME AND BIOCHEMICAL INDICATORS OF ORAL FLUID IN PERIODONTITIS IN PATIENTS WITH RHEUMATOID ARTHRITIS - O. Syniachenko; M. Iermolaieva; S. Iarova; D. Gaviley; K. Liventsova; S. Verzilov; T. Aliieva (Український стоматологічний альманах)
Infection with comorbid periodontitis due to transient bacteremia in patients with rheumatoid arthritis (RA) can lead to microbial colonization outside the mouth and increase systemic immune inflammation. Periodontitis-induced endotoxemia increases the sensitivity of RA patients to autoantigens by activating membrane proteins, pro-inflammatory enzymes, and cytokines. RA and periodontitis have similar osteoclasia, allelic genes and general imbalance in the state of the cytokine network, and carbamylation of proteins and the formation of extracellular traps of neutrophils are associated with simultaneous autoimmune imbalance in the combination of RA and periodontitis, but the listed pathogenetic mechanisms require further study.